The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1002/ajh.20317
|View full text |Cite
|
Sign up to set email alerts
|

Von Willebrand factor antigen levels in Behçet disease

Abstract: High von Willebrand factor antigen (vWF:Ag) levels can be found due to vascular endothelial injury in Behç et disease. The aim of this study is to evaluate whether there is any relationship between vWF:Ag levels and vascular or other organ involvements and acute-phase reactants in Behç et disease. Fifteen controls and 17 Behç et's patients were included; 10 had oral ulcers, 5 had genital ulcers, 3 had skin lesions, 6 had ocular involvement, 5 had arthritis, and 6 had vascular involvement. VWF:Ag levels were hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…[44][45][46] Moreover, high levels of serum concentration of von Willebrand factor (vWF, an endothelial product that is shown in yellow in Figure 4), plasminogen activator inhibitor-1, and thrombomoduline were found in patients with BD. 47,48 Along this line, Demirer et al, 46 Ozoran et al, 47 and Beyan et al 49 showed that the level of vWF was significantly higher in patients with BD, supporting endothelial destruction because of vasculitis related with BD. 50 Factor V Leiden (F5) mutation was also reported as associated with thrombosis in BD.…”
Section: Focal Adhesionmentioning
confidence: 76%
“…[44][45][46] Moreover, high levels of serum concentration of von Willebrand factor (vWF, an endothelial product that is shown in yellow in Figure 4), plasminogen activator inhibitor-1, and thrombomoduline were found in patients with BD. 47,48 Along this line, Demirer et al, 46 Ozoran et al, 47 and Beyan et al 49 showed that the level of vWF was significantly higher in patients with BD, supporting endothelial destruction because of vasculitis related with BD. 50 Factor V Leiden (F5) mutation was also reported as associated with thrombosis in BD.…”
Section: Focal Adhesionmentioning
confidence: 76%
“…Previous reports found contradicting results regarding the correlation between vWF plasma level and active vasculitis (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Most of the studies, however, were small retrospective case series, with varying non-validated de nitions for active vasculitis and remission (16,20,21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Increased serum levels of vWF antigen in different systemic vasculitides have been demonstrated in various studies, including in Kawasaki disease (11)(12)(13)(14), childhood primary CNS vasculitis (6), polymyalgia rheumatica (15), giant cell arteritis (15)(16)(17), granulomatosis with polyangiitis (18, 19), microscopic polyangiitis (19), Henoch-Schönlein purpura (20)(21)(22), Takayasu arteritis (23) and Behçet's disease (24). Most of these studies, however, are small retrospective case series that did not use validated outcome measures (16,(20)(21)(22)(23), and vWF Ag serum levels were not corrected to blood groups.…”
Section: Introductionmentioning
confidence: 99%
“…105 More recently, significantly higher vWF: Ag levels were reported in BD patients compared to a control group. 106 There was no statistically significant difference between vWF: Ag levels in patients with and those without organ involvement. A significant linear correlation between high vWF: Ag and serum ferritin levels was observed, suggesting that vWF: Ag was related to disease activity.…”
Section: Coagulation Factorsmentioning
confidence: 94%
“…A significant linear correlation between high vWF: Ag and serum ferritin levels was observed, suggesting that vWF: Ag was related to disease activity. 106 BD with deep vein thrombosis and the factor V Leiden mutation has been reported. 107 However, others authors have not found any association between three thrombogenic mutations (factor V gene G169IA, methylenetetrahydrofolate reductase gene C677T, and prothrombin G →A 20210 mutation) and BD patients with thrombosis.…”
Section: Coagulation Factorsmentioning
confidence: 97%